The monologic imagination - Tomlinson, Matt 1970-; Millie, Julian 1967- (Oxford studies in the anthropology of language, 2017)
The pioneering work of Bakhtin has led scholars to see all discourse as "dialogical." Contributors to this volume argue that something is overlooked with this focus. Many speakers, especially in political and religious contexts, craft monologues-single-voiced statements to which the only expected response is agreement or faithful replication.